Factors associated with fruit and vegetable and total fat intake in university students: A cross‐sectional explanatory study. Issue 2 (4th January 2018) - Deliens, Tom; Verhoeven, Hannah; De Bourdeaudhuij, Ilse; Huybrechts, Inge; Mullie, Patrick; Clarys, Peter; Deforche, Benedicte
Abstract : Aim: This study assessed sociodemographics, general health, personal and environmental factors associated with fruit and vegetable (F&V) and total fat intake in Belgian university students. Methods: In total, 185 students completed a self‐reported online questionnaire assessing daily F&V and fat intake, as well as sociodemographic, personal and environmental variables related to F&V and fat intake. Mean F&V and fat consumption were compared with Belgian recommendations. Multiple linear regression analyses were conducted to identify factors associated with F&V and fat intake. Results: Respectively, 90.3 and 50.8% of students failed to meet the recommendations for F&V and fat consumption. Agreeing more with the fact that one should eat F&V on most days of the week (individual subjective norm), finding it less difficult to eat F&V at home or at university (perceived behavioural control) and experiencing more modelling were associated with higher F&V consumption. Increasing age, higher educational level of the father and higher individual subjective norm about eating low‐fat foods were associated with lower fat intake. Conclusions: Future interventions aiming to improve dietary intake among university students should focus on younger students with lower socioeconomic status and should enhance students' subjective norm and behavioural control concerning healthy eating.